A novel polymorph of gadolinium tetrahydroborate produced by mechanical milling - Andrade Gamboa, Julio José (2010)
Gadolinium tetrahydroborate produced by mechanochemical processing of LiBH4–3GdCl3 mixture exhibits a structural transformation at 484 K. The high-temperature structure has a type cubic structure Gd(BH4)3 (a = 11.418 Å), which is isostructural with the one recently reported for Ce(BH4)3. This new phase remains upon heating up to 503 K. Combination of thermal hydrogen desorption, DSC, PXRD and FTIR allows to determine that the thermal decomposition of high-temperature structure Gd(BH4)3 starts above 503 K and leads to 3.1 wt% of hydrogen release obtaining mainly GdH2 as final decomposition product.